Gut microbiota’s causative relationship with peripheral artery disease: a Mendelian randomization study - Tian, Yu; Yao, Guanqun; Skudder-Hill, Loren; Xu, Guangyang; Qian, Yuxuan; Tang, Feng; Wang, Qian; Bao, Qianhui; Li, Lei (Frontiers in Microbiology, 2024)
The relationship between gut microbiota and peripheral artery disease (PAD) remains understudied.While traditional risk factors like smoking and hyperlipidemia are well-understood, our study aims to determine the potential causative association of gut microbiota with PAD using Mendelian Randomization.Methods: Data from the International MiBioGen Consortium and the FinnGen research project were used to study 211 bacterial taxa. Instrumental variables, comprising 2079 SNPs, were selected based on significance levels and linkage disequilibrium. Analyses were conducted utilizing the inverse-variance weighted (IVW) method and other statistical MR techniques to mitigate biases, processed in R (v4.3.1) with the TwosampleMR package.Three bacterial taxa, namely genus Coprococcus2, RuminococcaceaeUCG004, and RuminococcaceaeUCG010, emerged as protective factors against PAD. In contrast, famil. FamilyXI and the genus Lachnoclostridium and LachnospiraceaeUCG001 were identified as risk factors.Our findings hint at a causative association between certain gut microbiota and PAD, introducing new avenues for understanding PAD's etiology and developing effective treatments. The observed associations now warrant further validation in varied populations and detailed exploration at finer taxonomic levels.